Effects of experience, knowledge and skill on regulating the performance of futsal passing actions - da Silvia, S.L.; Travassos, B.; Davids, K.; Moreira, A.; Antonia Sabino da Silva, F.; Corrêa, U. C. (International Journal of Sport Psychology, 2017)
This study investigated how individuals with different levels of experience, knowledge, and skill made decisions on passing the ball during competitive games of futsal, based on information about angular interpersonal coordination with teammates and opponents. For this purpose, we analysed 80 passes performed by 40 male players (M = 13.0 years, SD = 0.7) differentiated by levels of experience, knowledge, and skill. Results revealed that: (1) players with low levels of knowledge performed successful passes with higher initial angular values than unsuccessful passes; and (2), experienced and skilful players completed successful passes based on information of the variability of emergence of angular interpersonal coordination. The findings revealed the attunement of players to the emergent dynamics of relationships with their teammates, and their teammates' marking defenders, as a crucial aspect of effective decision-making on where and whom to pass to.